2019
DOI: 10.36011/cpp.2019.1.e2
|View full text |Cite
|
Sign up to set email alerts
|

Asian Cohort Studies on Cardiovascular Risk Factors in Childhood

Abstract: Long-term cohort studies have shown that cardiovascular risk factors measured during childhood were associated with levels of adult cardiovascular risk factors and also with the lifetime risk of cardiovascular disease (CVD). However, most of the epidemiologic evidence was from Western studies and relatively small in the Asian population. From the literature, we identified and reviewed 8 Asian cohort studies focusing on cardiovascular risk factors among children. The Asian cohort studies have confirmed that chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…In the first issue, Jung et al 1) showed the result of Asian cohort study on cardiovascular risk factors in childhood. In the article, childhood risk factors can predict later levels of adult risk factors.…”
mentioning
confidence: 99%
“…In the first issue, Jung et al 1) showed the result of Asian cohort study on cardiovascular risk factors in childhood. In the article, childhood risk factors can predict later levels of adult risk factors.…”
mentioning
confidence: 99%